Coca-cola : marketing to billions in China. - Goh, Mui Yen. (2008)
Coca-Cola: Marketing to Billions in China. This is a case of a soft drink phenomenon coming face to face with the largest market in the world. The main objective of our study stems from several factors. Firstly, China's immense potential as the world's most important emerging market, and fastest evolving economy draws our attention to this region. Also, this is a classic case of ‘east meet west’ culture diffusion and it is interesting to explore the marketing prowess of Coca-Cola in an unfamiliar ground and how its culture has been able to reign successfully in the Chinese market.